2023
DOI: 10.1002/mus.27935
|View full text |Cite
|
Sign up to set email alerts
|

What do people affected by amyotrophic lateral sclerosis want from health communications? Evidence from the ALS Talk Project

Abstract: Introduction/AimsHealth communication is central to effective, supportive amyotrophic lateral sclerosis (ALS) clinical care. Guidance for ALS communication is limited, focuses on diagnosis disclosure, and frequently relies on expert consensus and/or reviews. Patient‐based evidence is needed to guide ALS health communication. We investigated how the experiences of ALS patients and family caregivers can inform effective communication practices from diagnosis to end‐of‐life.MethodsData were drawn from the ALS Tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
(205 reference statements)
0
0
0
Order By: Relevance
“…This triangulation seemed to be valuable to carers. Indeed, other MND studies showed overwhelming positive responses from carers [ 26 ] in engaging with therapies and HCPs in communicating [ 27 ] well and supporting their experience of caring for a PwMND [ 23 ]. Future service design should take carers’ needs into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This triangulation seemed to be valuable to carers. Indeed, other MND studies showed overwhelming positive responses from carers [ 26 ] in engaging with therapies and HCPs in communicating [ 27 ] well and supporting their experience of caring for a PwMND [ 23 ]. Future service design should take carers’ needs into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that a modulation of HCP involvement would be ideal, with HCPs responding to carers’ need in a dynamic way. Nuanced communications, tailored for the carer, seems to be a good way forward in response to carers’ experiences reported in MiNDToolkit and the scientific literature [ 27 ]. HCPs should be reminded that carers place great value on their input, time, and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…These assumptions and perceptions, which partly stemmed from HCPs’ lack of training and confidence in identifying behavioral symptoms and providing follow-on support, highlight the need for HCPs to receive specialist training. With recent evidence suggesting that PlwMND and carers rely on clinicians for medical and practical information ( 15 ), it is vital that HCPs receive appropriate training and resources for the management of behavioral symptoms. In addition, it is important that discussions on communication preferences in response to changing needs and disease progression are held early in the therapeutic relationship to eliminate assumptions which might hinder the provision of support ( 15 ).…”
Section: Discussionmentioning
confidence: 99%